Petrogenetic constraints on magma fertility in the Baguio Mineral District, Philippines: Probing the mineralization potential of the igneous host rocks in the Sangilo epithermal deposit - Jabagat, Karl D (Archīum Ateneo, 2020)
In the Baguio Mineral District (BMD), porphyry Cu ± Au deposition and associated epithermal mineralization are attributed to the highly evolved magmatism during the Pliocene. It has been well-documented that the interaction between silicic crustal melts and primitive mantle melts formed water-rich, oxidized magmas that resulted to hydrothermal mineralization. However, there are very few studies on the Early to Middle Miocene calc-alkaline magmatism which is considered to be barren of mineralization. This magmatic event is represented by phases of the Central Cordillera Diorite Complex (CCDC), which also serve as host rocks to the Sangilo epithermal deposit. The Sangilo quartz-carbonate veins in the BMD are hosted by an Early Miocene hornblende diorite (22.33 ± 0.63 Ma) intruded by a Middle Miocene quartz diorite (15.91 ± 0.6 Ma) which are, in turn, penetrated by Pliocene basaltic andesite dikes. The Miocene magmatic units with hybrid crust-mantle source affinity were formed from varying degrees of interaction within the MASH (mixing, assimilation, storage, and homogenization) zone during the formation of the CCDC. The basaltic andesite dikes, part of the Pliocene Mafic Dike Complex, represent direct differentiates of basaltic melts that experienced ponding at the base of the lower crust before ascending to shallow crustal levels. Based on the assessment of the physico-chemical conditions, three distinct magmatic events were identified: a barren Early Miocene event, a fertile Middle Miocene event and a fertile Pliocene event. The Middle Miocene fertile magmatism is attributed to further development of the MASH zone under the Luzon arc from the Early to Middle Miocene. On the other hand, the enhanced fertility during the Pliocene is associated with the subduction of the Scarborough Ridge. In the Baguio Mineral District (BMD), porphyry Cu __ Au deposition and associated epithermal mineralization are attributed to the highly evolved magmatism during the Pliocene. It has been well-documented that the interaction between silicic crustal melts and primitive mantle melts formed water-rich, oxidized magmas that resulted to hydrothermal mineralization. However, there are very few studies on the Early to Middle Miocene calc-alkaline magmatism which is considered to be barren of mineralization. This magmatic event is represented by phases of the Central Cordillera Diorite Complex (CCDC), which also serve as host rocks to the Sangilo epithermal deposit. The Sangilo quartz-carbonate veins in the BMD are hosted by an Early Miocene hornblende diorite (22.33 __ 0.63 Ma) intruded by a Middle Miocene quartz diorite (15.91 __ 0.6 Ma) which are, in turn, penetrated by Pliocene basaltic andesite dikes. The Miocene magmatic units with hybrid crust-mantle source affinity were formed from varying degrees of interaction within the MASH (mixing, assimilation, storage, and homogenization) zone during the formation of the CCDC. The basaltic andesite dikes, part of the Pliocene Mafic Dike Complex, represent direct differentiates of basaltic melts that experienced ponding at the base of the lower crust before ascending to shallow crustal levels. Based on the assessment of the physico-chemical conditions, three distinct magmatic events were identified: a barren Early Miocene event, a fertile Middle Miocene event and a fertile Pliocene event. The Middle Miocene fertile magmatism is attributed to further development of the MASH zone under the Luzon arc from the Early to Middle Miocene. On the other hand, the enhanced fertility during the Pliocene is associated with the subduction of the Scarborough Ridge.